A plataforma Makemusic Cloud na prática deliberada da afinação no violoncelo: estudos com cromatismo, atonalismo, cordas duplas e ausência de cordas soltas - Pedro Henrique Ludwig (2023)
In order to achieve expertise in music performance, many hours of practice are necessary. The use of new technologies in the development of technical and artistic skills has the potential to give more autonomy and optimize the time of students and teachers, making learning more efficient. Thus, the MakeMusic Cloud® online platform offers several resources to aid the learning of musical performance, especially (1) the realization of accompaniment for a vast repertoire of pieces and methods, (2) concomitant feedback regarding tuning and rhythm, and (3) a music score editor that offers students and teachers the possibility to create their own exercises. Intonation is one of the most important skills in the performance of bowed string instruments. Relevant evidence on this topic, from the point of view of acoustics, psychoacoustics, cognition and music education- in addition to concepts from the area of motor learning- form the theoretical framework of this work. This thesis, with a creative approach and qualitative evaluation, proposes an investigation of deliberate practice using MakeMusic Cloud® for the improvement of intonation in the intermediate and advanced level repertoire on the cello. For this, exercises were created for the practice of excerpts of difficult intonation in works by Bach, Brahms, Saint-Saëns, Popper, Kabalevsky and Crumb with the following characteristics: (1) absence of open strings, (2) double stops, (3) chromaticism, and (4) atonality.